Pengaruh Social Electronic Word Of Mouth (Ewom) Terhadap Keputusan Pembelian Melalui Brand Image Lazada (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Trunojoyo Madura) - Mamlu’atul Mawadah; Yudhi Prasetya Mada (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study aims to determine the effect of Social eWOM on Brand Image, determine the effect of Social eWOM on Purchase Decisions, determine the effect of Brand Image on Purchase Decisions, and determine the influence of Social eWOM on Purchase Decisions through Brand Image on Lazada users at the Faculty of Economics and Business, Trunojoyo University Madura.The sample used in this study were 97 respondents who had shopped at Lazada. The sample was selected by purposive sampling method. The analytical techniques used were descriptive analysis, validity, reliability, classical assumptions, and path analysis.The results of this study indicate that: (1) Social eWOM (X) has a significant direct effect on Brand Image (Z) (2) Social eWOM (X) has a direct significant effect on Purchase Decisions (Y) (3) Brand Image(Z) has a direct significant effect on Purchase Decision (Y). (4) Social eWOM (X) has a significant indirect effect on Purchase Decisions (Y) through Brand Image (Z). The results of the path coefficients show that there is a significant relationship between (X→Z) Thus, it can be stated that Social eWOM (X) indirectly has a significant effect on Purchase Decision (Y) through Brand Image (Z) with an effect of 0.266 or 26.6%